A Randomized Clinical Trial of Multimodal Therapy and Mulligan’s Concept of Manual Therapy for Patients with Chronic Pain Syndrome Caused by Upper Cervical Spine Disorders - Put, Marcin; Huber, Juliusz; Pieniazek, Marek; Gadek-Michalska, Anna; Szczygiel, Andrzej (International Journal of Orthopedics and Rehabilitation, 2016)
Study Design: A randomized, parallel-group clinical trial, 2 weeks treatment period with follow-up reassessment after therapy. Objectives: To compare the relative efficacy of multimodal rehabilitation and Mulligan’s concept of manual therapy for patients with chronic neck pain and cervicogenic headache. Background: Cervicogenic headache and neck pain are the main syndromes caused by upper cervical musculosceletal disorders (C0-C3). According to clinical researches for about 20% of the patients with chronic unilateral headache, the cause is of the cervical origin. Relatively little is known about the efficacy of Mulligan’s concept of manual therapy for patients with chronic pain syndrome caused by upper cervical spine disorders. Methods: Patients (n=104) with chronic pain syndrome caused by upper cervical spine disorders, were randomized into two groups: multimodal therapy (massage, electrotherapy, ultrasound) and Mulligan’s concept of manual therapy group. Outcomes: pain intensity (VAS), neck disability index (NDI), range of motion (ROM). Results: Both groups (multimodal therapy and Mulligan’s concept) showed significantly reduced pain and disability, but the effect between groups wasn’t significantly superior with either therapy alone. Mulligan’s concept of manual therapy showed greater gains in range of motion; extension (p=0.01), left rotation (p=0.01) and right rotation (p=0.03) than the multimodal therapy. Conclusion: Mulligan’s techniques are an effective method in the management of upper cervical spine disorders.